Research on Theories and Methods of Vehicle Sound Source Recognition. (October 2019) - Xiong, Jianqiang
Abstract: In this paper, the theory of vehicle noise source identification is studied and analyzed, based on the theory of various noise sources identification, the theory of vehicle noise source identification is divided into traditional noise source identification method, signal analysis-based noise source identification method and visualization-based noise source identification method. The basic principle, process, advantages and disadvantages of the three kinds of noise source identification theory described in this paper, as well as the application and selection analysis of the suitable situation are mainly described. Finally, it is pointed out that the application of visualization technology will be the main development trend of vehicle noise source identification theory.